Gaṅgeśaʼs philosophy of God : analysis, text, translation, and interpretation of Īśvaravāda section of Gaṅgeśaʼs Tattvacintāmaṇi with a study of the development of Nyāya theism - Vattanky, John (Adyar Library series ;, 1984)
On the position of God, according to the Nyāya school in Hindu philosophy, as found in the Īśvaravāda section of Tattvacintāmaṇi by Gaṅgeśa, 13th cent.